Human exposure to bisphenol AF and diethylhexylphthalate increases susceptibility to develop differentiated thyroid cancer in patients with thyroid nodules. (March 2019) - Marotta, Vincenzo; Russo, Giacomo; Gambardella, Claudio; Grasso, Marica; La Sala, Domenico; Chiofalo, Maria Grazia; D'Anna, Raffaella; Puzziello, Alessandro; Docimo, Giovanni; Masone, Stefania; Barbato, Francesco; Colao, Annamaria; et al.
Abstract: Pollutants represent potential threats to the human health, being ubiquitous in the environment and exerting toxicity even at low doses. This study aims at investigating the role of fifteen multiclass organic pollutants, assumed as markers of environmental pollution, most of which exerting endocrine-disrupting activity, in thyroid cancer development. The increasing incidence of differentiated thyroid cancer (DTC) may be related to the rising production and environmental dissemination of pollutants. Fifty-five patients, twenty-seven with diagnosis of benign thyroid nodules and twenty-eight suffering from differentiated thyroid cancer, were enrolled and the concentration levels of seven bisphenols, two phthalates ( i.e. di(2-ethylhexyl) phthalate (DEHP) and its main metabolite, mono-(2-ethyl-hexyl) phthalate) (MEHP)), two chlorobenzenes, (1, 4-dichlorobenzene and 1, 2, 4, 5-tetrachlorobenzene), and 3 phenol derivatives (2-chlorophenol, 4- nonylphenol, and triclosan) were determined in their serum by using a validated analytical method based on high performance liquid chromatography with ultraviolet tandem fluorescence detection. A significant relationship was found between malignancy and the detection in the serum of both bisphenol AF and DEHP. Indeed, their presence confers a more than fourteen times higher risk of developing differentiated thyroid cancer. Relationship between these two pollutants and the risk of malignancy was dose-independent and not mediated by higher thyroid stimulating hormone levels. Even if a conclusive evidence cannot still be drawn and larger prospective studies are needed, the exposure to low doses of environmental endocrine-disrupting contaminants can be considered consistent with the development of thyroid cancer. Graphical abstract: Image Highlights: A study investigating the role of fourteen multiclass organic pollutants. Serum analysis of 55 patients, 27 with benign nodules and 28 with DTC. Significant relationship between malignancy and serum detection of BPAF and DEHP.